How do Chinese undergraduates understand critical thinking? A phenomenographic approach - Zhao, Xiantong; Liu, Xu (Frontiers in Education, 2022)
The cultivation of critical thinking in undergraduates is crucial for teaching in higher education. Although scholars have defined critical thinking in various ways, limited study about critical thinking from the learner’s perspective. In this phenomenographic research, we collect essays written by 80 Chinese undergraduates with multiple disciplinary backgrounds to reveal their understandings of critical thinking. Four conceptions of critical thinking were found, namely critical thinking as query and reflection on the irrationality of things (Conception 1); an objective and comprehensive understanding of things (Conception 2); independent thinking with innovation (Conception 3), as well as a willingness and attitude (Conception 4). Further analysis in the light of the referential-structural framework helps to construct a hierarchical relationship between different conceptions, with Conception 1 the least complex and Conception 3 the most complex. While Conceptions 1–3 are skill-oriented, Conception 4 is deposition-oriented, and there is no hierarchical relationship between the two groups of conceptions. They deal with different dimensions of critical thinking. University lecturers can use these findings to help equip undergraduates with deepened conceptions of critical thinking in their daily routine teaching.